Melayani Tuhan di Tempat Kerja - Sugiyarto, Iskak (Sekolah Tinggi Teologi Kanaan Nusantara, 2021)
The adaptation of new habits due to the corona virus pandemic applies to the world community and Indonesia. Adaptation affects the relationship between individuals, so that the pattern of interaction in society requires adjustment. This is no exception for churches and Christian institutions in service to the congregation and to society. Service models with the old approach - especially before the corona virus pandemic - need to be evaluated to find patterns that fit the community in this new normal. Therefore, this study wants to find out how churches and Christian institutions should serve in adapting new habits during this corona virus pandemic? How does the church involve a congregation of mostly lay and secular workers serving in the world of work? By using a study of literature or literature, it is expected to find a pattern of church service (eklesia) that is in accordance with the conditions of today's society. From literature studies and previous research, it was found that a growing church is a church that does not only rely on